Pengemasan dan Penyimpanan Dingin Kelapa Kopyor untuk Mempertahankan Mutu - Muhammad Yusuf Antu; Rokhani Hasbullah; Usman Ahmad (Jurnal Keteknikan Pertanian, 2014)
AbstractThe objectives of this research were to study the influence of packaging material and the temperature applied during storage on the quality of kopyor coconut, to predict the shelf-life, and to determine the best packaging material and the storage temperature to keep the kopyor coconut. Research material is kopyor coconut obtained from Kalianda South Lampung. Kopyor coconut packaged in plastic film type Polyamide (PA), Polypropylene (PP), and High Density Polyethylene (HDPE) each weighing 60g. The quality parameter observed are free fatty acids (FFA), total microbes, and sensory characteristics including color, flavor, and taste. This research us Randomized Complete Design with two factors. The first factor was the packaging material with three different types (PA, PP, HDPE), and the second factor was the storage temperature at two levels of 5±2OC and 10±2OC. The shelf-life was predict using Partially StaggeredDesign (PSD) technique. Principal Component Analysis (PCA) technique was used to determine the best treatment. The results showed that the type of plastic packaging and storage temperature gave an effect onthe total microbes, and organoleptics of color, flavor, and taste. PA packaging is the best packaging can be maintained the quality of organoleptic and reduce the microbe growth. The storage temperature of 5±2OC can maintain quality of kopyor coconut better than 10±2OC temperature. Based on PSD method and total microbe as critical parameters, the shelf-life of kopyor coconut at 5±2OC is 27, 26, and 17 days for plastic PA, HDPE, and PP packaging, respectively.Keywords: kopyor coconut, packaging, film plastic, shelf-life.AbstrakTujuan penelitian adalah untuk mempelajari pengaruh jenis kemasan dan suhu penyimpanan terhadap mutu kelapa kopyor, memprediksi umur simpan, dan menentukan jenis kemasan dan suhu terbaik untuk menyimpan kelapa kopyor. Bahan penelitian adalah kelapa kopyor diperoleh dari Kalianda Lampung Selatan. Kelapa kopyor dikemas plastik jenis Polyamide (PA), Polypropylene (PP), dan High Density Polyethylene (HDPE) masing-masing seberat 60g. Parameter mutu yang dianalisis adalah Asam Lemak Bebas (ALB), total mikroba, dan organoleptik warna, aroma, dan rasa. Penelitian menggunakan Rancangan Acak Lengkap dengan dua faktor. Faktor pertama adalah plastik dengan tiga taraf (PA, PP, HDPE), dan faktor kedua adalah suhu dengan dua taraf (5±2OC dan 10±2OC). Prediksi umur simpan menggunakan Partially Staggered Design (PSD). Untuk menentukan perlakuan terbaik digunakan Principal Component Analysis (PCA). Hasil penelitian menunjukkan bahwa jenis kemasan plastik dan suhu penyimpanan berpengaruh nyata terhadap total mikroba, dan organoleptik warna, aroma, dan rasa. Kemasan jenis PA merupakan yang terbaik dalam mempertahankan mutu organoleptik dan menekan pertumbuhan mikroba. Suhu penyimpanan 5±2OC lebih dapat mempertahankan mutu kelapa kopyor dibandingkan dengan suhu10±2OC. Berdasarkan metode PSD dengan menggunakan mutu kritis total mikroba, umur simpan kelapa kopyor pada suhu 5±2OC adalah 27, 26, dan 17 hari untuk kemasan plastik PA, HDPE, dan PP.Kata kunci: kelapa kopyor, pengemasan, plastik film, umur simpan.Diterima: 18 Maret 2014 ; Disetujui;16 Juli 2014